2012
DOI: 10.4236/ns.2012.411110
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> evaluation of antioxidant and antibacterial activities of extracts of <i>Hertia cheirifolia’s</i> leaves

Abstract: In this study, our objective is to investigate the antioxidant activity by the means of two methods: the β-carotene bleaching method and DPPH assay as well as testing the antibacterial activity by the Agar-well diffusion method, of the extracts (EEp, EDm, EMe and EAq) from the sheets of Hertia cheirifolia. The quantitative analysis are showed that the highest content of total phenolic was concentrated in the methanolic extract with 30.33 ± 2.82 μg EAG/mg of extracts, in the second level the EAq extract and EDm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous study also demonstrated that the methanol extract from the same plant had a strong ability to act as antiradical (Bousselsela et al. 2012 ). In addition, both extracts exhibited chelating capacity, and the activity of the aqueous extract was unexpectedly better than that of methanol extract; in perfect contrast to those found for free radical scavenging.…”
Section: Discussionmentioning
confidence: 80%
“…Previous study also demonstrated that the methanol extract from the same plant had a strong ability to act as antiradical (Bousselsela et al. 2012 ). In addition, both extracts exhibited chelating capacity, and the activity of the aqueous extract was unexpectedly better than that of methanol extract; in perfect contrast to those found for free radical scavenging.…”
Section: Discussionmentioning
confidence: 80%
“…22,49 The presence of hydroxylated chemicals, such as monoterpenes (α-pinene, camphene, sabinene, limonene, linalool, and verbenol) and sesquiterpenes (germacrene D, α-muurolene, and spathulenol) in the sample could account for the potent inhibitory ability of the essential oil. 50–53 Compared with the results of previous studies on the same plant, 11,18,21,22,25 we note that there is a difference in the results obtained. However, according to previous studies, these differences in antioxidant capacity could be due to several factors, including the molecular nature of bioactive compounds.…”
Section: Resultsmentioning
confidence: 52%
“…17 In fact, literature studies indicate that H. cheirifolia possesses biological activities. [18][19][20][21][22][23][24][25] Moreover, it is recommended for use as a mosquito control since it is successful against larval stages. 26 To the best of our knowledge, however, no research has investigated the phytochemical constituents and pharmacological properties of the EO (essential oil) found in the aerial parts of H. cheirifolia growing in the Aures area (Algeria), and, in particular, no prior studies have looked at the antifungal potential of the EO of this species, and its association with the mycelial growth of FOL.…”
Section: Introductionmentioning
confidence: 99%
“…The methanolic and chloroformic extracts of the aerial parts of H. pallens contain a large amount of sesquiterpenes [1]. The methanolic extract of H. cheirifolia has significant antioxidant activity [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The methanolic extracts of H. cheirifolia have moderate antibacterial activity [15][16][26][27], whereas Bousselsela et al [13] reports that oils of this species are ineffective against most bacterial strains tested. The essential oil of H. maroccana is considered moderately active against gram-negative and those of grampositive [9].…”
Section: Introductionmentioning
confidence: 99%